Competency Modeling at an International Freight Forwarding Company in Bangkok, Thailand - Kunte, Manjiri; Sarika, Wattana (Asia Social Issues, 2023)
This study presents a competency modeling exercise conducted at a company located in Bangkok, Thailand. The company provides international logistics and freight forwarding services. The findings of this study include the key competencies and competency gaps, as well as the organization development methods to fill those competency gaps. The study identifies the need for competency modeling and management based on the company’s strategic plan. Based on the review of the literature and the identification of one in-depth interview and multiple focus groups as the data collection method, a competency modeling process is devised. Referring to the data collected from the in-depth interviews and focus group discussions; the authors present the competency modeling process and identify the gaps for each job category. In the latter part of the study, the authors present the organization’s development methods, recommend ways to fill the competency gaps, and indicate the relevance of updating the competency scorecard every year. This study will be helpful for human resource managers, line managers, and supervisors in the logistics and supply chain industry. Moreover, the findings of this study will be helpful for the employees of such companies and their leadership and management alike. Considering the changes brought about by the pandemic, this study can be used by other logistics service providers as a benchmark for competency management.